The Effect of Disposable Water (Diaper) Usage Toward Toilet Training Behavior In Pre-School Children - Munjiati, Munjiati; Fitriyani, Aris; Walin, Walin (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Diaper is an option for most mothers because they are practical for the parents and make babies sleep better. Children who wear diapers often show late toileting development since they cannot feel a sense of damp when urinating. This study aimed to know the use of baby diapers on toilet training behavior of pre-school children in Early Childhood Education Programs (PAUD) and Kindergarten at Mersi village, Purwokerto. This was a non-experimental quantitative study with cross-sectional study design. The population was 217 children with history of diaper usage. The samples were 68 respondents who met the inclusion criteria. The data was analyzed using Chi Square. This research has already been conducted in 2013. The results showed that 85.4% respondents wore diapers, whereas 14.6% did not. 12.5% respondents had good toilet training behavior, 78% had sufficient behavior 78%, and 9.5% were lacking. There was a significant difference between history of diapers usage and toilet training behavior among pre-school children in Early Childhood Education Programs (PAUD) and Kindergarten at Mersi village (p=0,04). It can be concluded that there was a significant difference between the usage of baby diapers and toilet training behaviors in pre-school children.